In vivo silencing of miR‐125a‐3p promotes myelin repair in models of white matter demyelination. Issue 10 (12th March 2020) - Marangon, Davide; Boda, Enrica; Parolisi, Roberta; Negri, Camilla; Giorgi, Corinna; Montarolo, Francesca; Perga, Simona; Bertolotto, Antonio; Buffo, Annalisa; Abbracchio, Maria P.; Lecca, Davide
Abstract: In the last decade, microRNAs have been increasingly recognized as key modulators of glial development. Recently, we identified miR‐125a‐3p as a new player in oligodendrocyte physiology, regulating in vitro differentiation of oligodendrocyte precursor cells (OPCs). Here, we show that miR‐125a‐3p is upregulated in active lesions of multiple sclerosis (MS) patients and in OPCs isolated from the spinal cord of chronic experimental autoimmune encephalomyelitis (EAE) mice, but not in those isolated from the spontaneously remyelinating corpus callosum of lysolecithin‐treated mice. To test whether a sustained expression of miR‐125a‐3p in OPCs contribute to defective remyelination, we modulated miR‐125a‐3p expression in vivo and ex vivo after lysolecithin‐induced demyelination. We found that lentiviral over‐expression of miR‐125a‐3p impaired OPC maturation, whereas its downregulation accelerated remyelination. Transcriptome analysis and luciferase reporter assay revealed that these effects are partly mediated by the direct interaction of miR‐125a‐3p with Slc8a3, a sodium–calcium membrane transporter, and identified novel candidate targets, such as Gas7, that we demonstrated necessary to correctly address oligodendrocytes to terminal maturation. These findings show that miR‐125a‐3p upregulation negatively affects OPC maturation in vivo, suggest its role in the pathogenesis of demyelinating diseases and unveil new targets for future promyelinating protective interventions. Abstract : miR‐125a‐3p is upregulated in OPCs isolated from EAE mice spinal cord and in human active lesions. miR‐125a‐3p inhibition promotes remyelination in an animal model of demyelination. miR‐125a‐3p impairs OPC maturation by targeting Slc8a3 and Gas7.